Does multimodal perioperative pain management enhance immediate and short‐term outcomes after living donor partial hepatectomy? A systematic review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Hogan, Brian J; Pai, Sher‐Lu; Planinsic, Raymond; Suh, Kyung‐Suk; Hillingso, Jens G; Ghani, Shahi Abdul; Fan, Ka Siu; Spiro, Michael; Raptis, Dimitri Aristotle; Vohra, Vijay; Auzinger, Georg
Abstract: Background: The optimal analgesic strategy for patients undergoing donor hepatectomy is not known and the potential short‐ and long‐term physical and psychological consequences of complications are significant. Objectives: To identify whether a multimodal approach to pain of the donor intraoperatively enhances immediate and short‐term outcomes after living liver donation, and to provide international expert panel recommendations. Data sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. PROSPERO 2021 CRD42021260699. Results: Nine studies assessing multi‐modal analgesia strategies were included in a qualitative assessment. Interventions included local, regional, and neuro‐axial anesthetic techniques, pharmacological intervention (NSAIDs, COX‐2 inhibitors, ketamine, dexmedetomidine, and lidocaine), and acupuncture. Overall, there was a significant (40%) reduction in opioid requirement on day 1 and a significant reduction in pain scores in the intervention vs control groups. Significant reductions in either length of stay or post‐operative complications were demonstrated in four of nine studies. Conclusions: Opioid use for patients undergoing donor hepatectomy is likely to impact both their short‐ and long‐term outcomes. To reduce post‐operative pain scores, shorten length of hospital stay, and promote earlier post‐operative return of bowel function, we recommend that multi‐modal analgesia be offered to patients undergoing living donor hepatectomy. Further research is required to confirm which multi‐modal techniques are most associated with enhanced recovery in living liver donors.